Data curation: a study of researcher practices and needs - Level, Allison V., author; Oehlerts, Beth, author; Cranston, Catherine, author; McLure, Merinda, author; Culbertson, Mike, author; The Johns Hopkins University Press, publisher (Colorado State University. Libraries, 2014)
Colorado State University librarians conducted five focus groups with thirty-one faculty, research scientists, and research associates. The groups explored: (1) The nature of data sets that these researchers create or maintain; (2) How participants manage their data; (3) Needs for support that the participants identify in relation to sharing, curating, and preserving their data; and (4) The feasibility of adapting the Purdue University Libraries' Data Curation Profiles Toolkit interview protocol for use in focus groups with researchers. The authors report their review of related literature, themes that emerged from analysis of the focus groups, and implications for related library services.
Keywords: focus groups; data curation; data management; faculty; academic libraries